Measuring the efficiency of Spain's wineries through data envelopment analysis - Borlinič Gačnik, Maja; Prevolšek, Boris; Peláez-Verdet, Antonio; Cerezo-Medina, Alfonso; Rozman, Črtomir (Slovenian society informatika, 2023)
The research evaluates the efficiency of wineries in Spain using the DEA (Data Envelopment Analysis) model. The study utilizes the CCR (Charnes-Cooper-Rhodes) model within DEA, which assumes constant returns to scale. Input and output data from 848 wineries were collected and normalized for analysis. The results indicate that only one winery operated at maximum efficiency, achieving the best possible results compared to others. The findings highlight the importance of efficient processes, resource allocation, and management practices in achieving optimal performance. Further research could explore efficiency comparisons among wineries with different activities, such as diversification into tourism.
Keywords: DEA model; Spain's wineries; Agrarian economics; Efficiency measurement